Alcohol consumption among French physicians: A cross-sectional study. (1st January 2021) - Thiebaud, Pierre-Clément; Martin, Camille; Naouri, Diane; Le Joncour, Alexandre; Truchot, Jennifer; Yordanov, Youri
Highlights: Prevalence of hazardous alcohol consumption among French physicians is 12.6 %. Drugs use and fixed term contract are associated with hazardous alcohol consumption. Risky alcohol consumption seems similar between physicians and general population. Abstract: Background: Data regarding French physicians' alcohol behaviours are scarce and most studies address this issue within the population of either medical students or residents. We aim to describe and assess the prevalence of hazardous alcohol consumption among French physicians. Methods: A regional, cross-sectional, survey was conducted in 2018 using an online questionnaire among Parisian general practitioners and hospital doctors. Hazardous alcohol consumption was defined by an Alcohol Use Disorders Identification Test (AUDIT) score ≥ 8. Data were analysed in 2020. Results: Five hundred fifteen physicians completed the survey: 108 general practitioners and 407 hospital physicians. The median age was 40 years [32−55] and 59 % were women. They considered their physical and mental health as average or bad in 10 % and 8% of cases, respectively. The prevalence of hazardous alcohol consumption was 12.6 %. Among the 65 physicians with hazardous alcohol consumption, 27 (41.5 %) did not considered it as risky and four (6.2 %) mentioned a potentially negative impact on patients' care. Factors independently associated with hazardous alcohol consumption were illegal drugs consumption (OR 4.62 [2.05–10.37]) and fixed term contract for hospital doctors (OR 2.69 [1.14–6.36]). Conclusions: The prevalence of hazardous alcohol consumption among French physicians was 12.6 %. Illegal substance users and fix-termed contract hospital doctors were more likely to have risky alcohol consumption. A large-scale national study would confirm the factors associated with hazardous alcohol consumption and could explore the efficacy of preventive measures to insure the safety and health of physicians and their patients.